2008
DOI: 10.1007/s00259-008-0733-1
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDG PET for the lymph node staging of non-small cell lung cancer in a tuberculosis-endemic country: Is dual time point imaging worth the effort?

Abstract: Our study demonstrates that PET is more accurate than CECT in LN staging NSCLC patients in Taiwan where TB is still prevalent. Semi-quantitative SUV method or DTPI with RI does not result in better diagnostic accuracy than visual analysis of PET images.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
80
2
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(86 citation statements)
references
References 28 publications
3
80
2
1
Order By: Relevance
“…It is quite possible that patients with inflammatory lung disease had more false-positive lymph nodes with low to intermediate 18 F-FDG uptake and, thus, a higher-than-usual SUV was obtained for the highest accuracy. A visual interpretation is widely used for clinical PET interpretation of lymph node involvement [25][26][27][28][29][30][31]. Most of the previous comparative studies demonstrated that visual analysis of PET is superior or comparable to the semiquantitative method except for N3 lymph nodes [25][26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is quite possible that patients with inflammatory lung disease had more false-positive lymph nodes with low to intermediate 18 F-FDG uptake and, thus, a higher-than-usual SUV was obtained for the highest accuracy. A visual interpretation is widely used for clinical PET interpretation of lymph node involvement [25][26][27][28][29][30][31]. Most of the previous comparative studies demonstrated that visual analysis of PET is superior or comparable to the semiquantitative method except for N3 lymph nodes [25][26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…A visual interpretation is widely used for clinical PET interpretation of lymph node involvement [25][26][27][28][29][30][31]. Most of the previous comparative studies demonstrated that visual analysis of PET is superior or comparable to the semiquantitative method except for N3 lymph nodes [25][26][27][28][29]. On the other hand, according to our results, the diagnostic performance of the visual criterion ''localized FDG uptake'' was inferior to a semiquantitative criterion, SUVmax (p = 0.002 for N1-N3 and 0.001 for N1-N2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, in several studies, it has been proposed that dual-time-point (DTP) FDG PET/ CT may improve the accuracy of LN staging in NSCLC [6][7][8]. However, other studies reported that single-timepoint (STP) FDG PET/CT at 1 h after FDG injection was sufficiently useful for LN staging in NSCLC, and the usefulness of DTP PET/CT is still controversial [9][10][11].…”
Section: Introductionmentioning
confidence: 99%